2012 IEEE International Games Innovation Conference 2012
DOI: 10.1109/igic.2012.6329849
|View full text |Cite
|
Sign up to set email alerts
|

Gamification of citizen sensing through mobile social reporting

Abstract: Abstract-The explosion of user-generated content on the Social Web published from mobile devices has seen reporting applications grow in popularity from self-reporting style workout tracking applications like Fitocracy 1 to community reporting applications like FixMyStreet 2 . In this paper, we introduce the concept of social mobile reporting where a community of people report on issues within their environment. We discuss annotating contextual metadata to reports, and the use of gamification to create an enga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 12 publications
0
36
0
1
Order By: Relevance
“…While this technologically is a step forward it does not include any social data from inhabitants of the city. Concurrently there is also research looking at mobile social reporting applications that allow citizens to report on issues within their local environment [13] and IBM's Smarter Cities research aims to incorporate social elements. 2 In our research, we aim to allow people (building users or people living in an area) the opportunity to both report but also to be active in fixing the issues in their environment and this has led to the creation of the concept of citizen actuators.…”
Section: Smart Citiesmentioning
confidence: 99%
See 1 more Smart Citation
“…While this technologically is a step forward it does not include any social data from inhabitants of the city. Concurrently there is also research looking at mobile social reporting applications that allow citizens to report on issues within their local environment [13] and IBM's Smarter Cities research aims to incorporate social elements. 2 In our research, we aim to allow people (building users or people living in an area) the opportunity to both report but also to be active in fixing the issues in their environment and this has led to the creation of the concept of citizen actuators.…”
Section: Smart Citiesmentioning
confidence: 99%
“…In this work, it is a uni-directional communication between the building occupant and the system but in future work we would like to allow users to post photos issues or problems [7,13] which would hopefully engage users more with the system. Social media platforms could also offer building-users the ability to view the energy consumption of the building and offer comment if the consumption is unexpectedly high through dashboards and social media platforms.…”
Section: The Rise Of Social Mediamentioning
confidence: 99%
“…Reports Forum (Crowley et al, 2012) Crowley et al propose a framework for citizen reporting that incorporates a number of game elements. The framework consists of a forum and a mobile application.…”
Section: Top Designsmentioning
confidence: 99%
“…We attempt to further our current understanding of preparedness, in particular what it implies, once the business member has been added to a VBE as well as preparedness to members managing the VBE and the role of preparedness in the operational phase of a VBE. Gamification is has been applied in different domains recently [19,9,5], but most of the applications target individual users (players) using the application. In this paper we have shown that gamification concepts can be trivially applied to situations where target players are actually organizations and not just an individual.…”
mentioning
confidence: 99%